A PROSPECTIVE SURVEY OF APPROPRIATENESS OF PAIN PHARMACOTHERAPY MANAGEMENT IN POST-CESAREAN SECTION PATIENTS IN CIPTO MANGUNKUSUMO HOSPITAL - JOHAN; INSTIATY; NAFRIALDI; PURWOSUNU, YUDITIYA (International Journal of Applied Pharmaceutics, 2019)
Objective: In this study, we sought to assess the pattern of analgesic usage, adequacy of pain management, side effects, and analgesic drug interactions in the post-emergency cesarean surgery setting. Methods: This was a prospective observational study of 80 patients who underwent emergency cesarean surgery at the Obstetrics and Gynecology Department of the Rumah Sakit Umum Pusat Nasional Cipto Mangunkusumo (RSUPN-CM) between July 2015 and January 2016. Adequacy of pain management during the first 3 post-operative days was assessed using Pain Management Index. Relation between pain intensity during activities and rest with patient characteristic was assessed using Chi-squared test and Fischer’s exact test. Results: Nineteen patients (8.7%) were prescribed two types of nonsteroid anti-inflammatory drugs concomitantly, and 41.8% received inappropriate analgesics at a lower frequency. Most patients experienced pain with numerical rating scale score >3 in the first 24 h post-surgery: 59 patients (73.75%) experienced pain during activities and 7 patients (8.75%) during rest. Conclusion: Post-emergency cesarean surgery pain management at RSUPN-CM was not optimal. Most patients did not receive adequate pain management in the first 24 h post-surgery.